Does Leadership Impact on Performance of Agriculture and Food Service? - Fitriana Windi Kinanti; I Ketut R Sudiarditha; Kasmir Kasmir (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2018)
This study aims to determine the effect of leadership, self-efficacy, and motivation on the performance of Wonogiri District Agriculture and Food Service employees. This study uses a quantitative approach. The object of this research is the performance of the Wonogiri District Agriculture and Food Service. Observation unit used 25 Agricultural Extension Centers. Determination of the sample using the cluster sampling method. The number of samples used was 218 samples. The method used is the survey method with questionnaires and interviews. The research design was descriptive, and the type of research used was explanatory research. Data analysis methods used include descriptive statistical analysis and parametric statistical analysis. The analysis technique uses Structural Equation Modeling (SEM). The results of the study showed leadership, self-efficacy and motivation had a positive effect on the performance of the Wonogiri District Agriculture and Food Service.